184k views
5 votes
Noah started to solve the equation-4.6p-6.3p+3.9=-9.18 below 1.combome like terms-10.9p+3.9=-9.18 apply the next steps to solve the equation.what is the solution

User LZR
by
5.3k points

1 Answer

4 votes
Hello!

Next, Noah will need to remove the term in thee equation, 3.9. He will do so by subtracting 3.9 from both sides.

-10.9p=-13.08

Now Noah will have to isolate the variable p. To do so he will divide both sides by -10.9.

p=1.2

I hope this helps!
User Jay Kim
by
5.9k points